Concomitant Haemophilus influenzae infection and anti- N-Methyl-D-Aspartate receptor encephalitis in a 7-year-old previously healthy girl: a case report - Abdul Rahman, Nurul Aimi; Mahayidin, Hasni; Tuan Soh, Tuan Suhaila; Ibrahim, Rosni (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Encephalitis is the inflammation of the brain which is usually caused by viral infections, but it can be also due to other non-infectious agents. We report an interesting case of anti-N-methyl-D-aspartate receptor (NMDAR) enceph- alitis with Haemophilus influenzae co-infection in association with severe acute respiratory syndrome coronavirus 2, without pulmonary involvement or fever.